Landfill site suitability using fuzzy multiple criteria decision analysis and geographical information system - Tibon, Noriza R.; Tanchuling, Maria Antonia N.; Blanco, Ariel C. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
With the growth of urbanization and population in the Philippines, larger amount of waste is produced leading to the major problem in solid waste disposal. Most of the municipal solid waste (MSW) generated in the country are disposed in dumpsites and landfills. However, many of these disposal facilities such as the Payatas Controlled Disposal Facility which is the repository of Quezon city's waste, have already reached their maximum capacity. In order to meet the city's landfilling needs, new locations must be sited. This study aims to present a methodological framework for identifying municipal landfill sites in the provinces of Bulacan and Rizal for Quezon City's waste. The framework involves fuzzy multiple criteria decision analysis (FMCDA) combined with the use of Geographical Information System (GIS) to aid in the site selection. Since siting a sanitary landfill requires extensive evaluation procedures to identify the best available landfill site, the procedure in this study employs every critical requirement such as that of the government regulations, with minimum impact in the environmental, social, and economic aspects. A final list of 14 factors and constraints along with their corresponding weights and attributes as obtained from the legislature, literature and experts' opinion were considered. Using magnitude method for defuzzification and Weighted Linear Combination for aggregation, a final suitability map was presented. Further, 26 areas were identified as highly suitable sites, 3 of which can be considered as potential candidate sites in accordance with economic viability as imposed by the government of Quezon City.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Sanitary landfills; Waste disposal sites -- Philippines